2000
DOI: 10.1002/1097-0215(20000901)87:5<734::aid-ijc17>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Role of alcohol dehydrogenase 3 and cytochrome P-4502E1 genotypes in susceptibility to cancers of the upper aerodigestive tract

Abstract: Alcohol is a recognized risk factor for upper aerodigestive tract (UAT) cancers, but the mechanism by which alcohol causes cancer remains obscure. Ethanol is oxidized to acetaldehyde (the suspected carcinogenic agent in alcohol) by alcohol dehydrogenases (ADHs) and cytochrome P‐4502E1 (CYP2E1), both of which exhibit great inter‐individual variability in activity. The hypothesis that these polymorphisms influence susceptibility to alcohol‐related cancers remains poorly documented. We investigated whether ADH3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 30 publications
6
43
1
1
Order By: Relevance
“…Even though liver metabolism in this study was excluded, effects of metabolites could not be disclaimed, because CYP 2E1 was found in normal, extrahepatal tissue, and in cancer cells, too (Kapucuoglu et al, 2003). Some variants of CYP 2E1 enzyme may play a role in the carcinogenesis of nasopharyngeal and pulmonal cancers (Bouchardy et al, 2000). CYP 2E1 was found in Caco-2 cells (Lampen et al, 1998), although there is no data on its presence or absence in other cell lines involved in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Even though liver metabolism in this study was excluded, effects of metabolites could not be disclaimed, because CYP 2E1 was found in normal, extrahepatal tissue, and in cancer cells, too (Kapucuoglu et al, 2003). Some variants of CYP 2E1 enzyme may play a role in the carcinogenesis of nasopharyngeal and pulmonal cancers (Bouchardy et al, 2000). CYP 2E1 was found in Caco-2 cells (Lampen et al, 1998), although there is no data on its presence or absence in other cell lines involved in this study.…”
Section: Discussionmentioning
confidence: 85%
“…[43][44][45] In the study of Bouchardy and colleagues, 43 121 patients with oral cancer and 129 with laryngeal cancer were compared with 172 control subjects. However, the allele frequency for ADH1C*1 in their controls was much higher than in our study and was almost similar to the ADH1C*1 allele frequency observed in our cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…39 40 Contradictory results have been reported with respect to the ADH1C genotype and UADTC. While one study from France 41 with a relatively small number of patients and another one performed in Puerto Rico, 42 a country known for its worldwide highest incidence of oral cancer, reported a positive correlation between ADH1C*1 allele frequency and the risk of developing UADTC, a larger French study 43 and a case control study from North Carolina 44 and Texas 45 did not confirm these findings. It has to be emphasised that in all of these epidemiological studies, individuals with a wide range of alcohol intake were analysed using predominantly interview techniques to quantitate alcohol consumption.…”
mentioning
confidence: 96%
“…Genetic polymorphisms of ethanol-metabolizing genes, such as acetaldehyde dehydrogenase (ALDH) and alcohol dehydrogenases (ADH), are associated with OESCC [1214]. Several studies have identified ALDH2*1/2 heterozygotes as a high-risk group for OESCC [15–19], and ADH genotypes not including ADH3 were associated with OESCC as well [13,20,21]. Tobacco use and alcohol drinking have synergistic effects on carcinogenesis; combined use explained more than 61% of OESCC [22,23].…”
Section: Overviewmentioning
confidence: 99%